Preparation and Acceptability of Guava Cheese - Singh, Harjinder; Kachwaya, Dilip Singh; Vikas, Ghumare (Journal of Postharvest Technology, 2016)
Guava cheese is the chewable confectionary item containing sugar and butter as the major ingredients. Seeds are removed and make fine pulp. According to recipe or treatment combinations the mixture heated up to 700Brix.Then citric acid and salt solution was added and heated up to 770Brix. Then allowed to cool and set. The organoleptic evaluation was carried out of prepared guava cheese. Present experiment was laid out in Completely Randomized Design (CRD) with five treatments viz. T1- Guava pulp (1kg) + Sugar (1 kg) + Ghee (100g), T2 - Guava pulp (1kg) + Sugar (1.2 kg) + Ghee ( 100 g), T3 - Guava pulp (1kg) + Jaggery (1kg) + Ghee (100 g), T4 - Guava pulp (1kg) + Jaggery (1.2 kg) + Ghee (100g), T5 - Guava pulp (1kg) +Artificial sweetener + Ghee (100 g) were used for formation of guava cheese. Each treatment was replicated four times. The results of the research shows that the guava cheese formed from use of Jaggery 1.2 kg along with 1kg guava pulp and 100g ghee shows good organoleptic rating (7.20) and better quality parameters. However the present investigation of use of different treatment combinations shows a non significant interaction between different treatment combinations. Thus treatment combination in which Jaggery 1.2 kg along with 1 kg guava pulp and 100g ghee was considered the most benefit tested one for formation and acceptability of guava cheese having good texture, colour and taste. This is less costly and farmers could easily adopt to increase their income by formation of guava cheese in the glut period.